Application of Delphi expert panel in joint venture projects - Adnan, H; Rosman, M R; Rashid, Z Z Ahmad; Yusuwan, N Mohamad; Bakhary, N A (IOP conference series. Earth and environmental science, 2018)
This study was conducted with the aim to identify the application of the Delphi Technique in validating findings obtained from questionnaire surveys and interviews done in- depth on the subject of joint venture projects in Malaysia. The Delphi technique aims to achieve a consensus of opinion amongst expert panellist that were selected on the primary factors in JV projects. To achieve research objectives, a progressive series of questions was designed where a selected panel of expert to confirm and validate the final findings. The rationale, benefits, limitations and recommendations for the use of Delphi were given in this study. From the literature review done, twenty-one factors were identified as critical factors to the making any joint venture project successful. Detail information from contractors were obtained by using the questionnaire survey method and forty-three in-depth interviews were carried out. Trust between partners, mutual understanding, partner selection criteria, agreement of contract, objective compatibility, conflict, and commitment were confirmed by the Delphi panel to be the critical success factors besides another fourteen factors which were found to be the Failure Reduction Criteria. Delphi techniques has proven to successfully assist in recognising the main factors and would be beneficial in supplementing the success of joint venture arrangements application for construction projects in Malaysia.